2006
DOI: 10.1017/s0001867800000823
|View full text |Cite
|
Sign up to set email alerts
|

Spinning plates and squad systems: policies for bi-directional restless bandits

Abstract: This paper concerns two families of Markov decision problem that fall within the family of (bi-directional) restless bandits, an intractable class of decision processes introduced by Whittle. The spinning plates problem concerns the optimal management of a portfolio of reward-generating assets whose yields grow with investment but otherwise tend to decline. In the model of asset exploitation called the squad system, the yield from an asset tends to decline when it is used but will recover when the asset is at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Further classes of indexable problems are the dual speed problem of Glazebrook, Nino-Mora, and Ansell [24], the maintenance models of Glazebrook, Ruiz-Hernandez, and Kirkbride [25], and the spinning plates and squad models of Glazebrook, Kirkbride, and Ruiz-Hernandez [23]. Our paper is in line with these works in that it trades indexability for specific structural conditions.…”
Section: Indexabilitysupporting
confidence: 62%
See 3 more Smart Citations
“…Further classes of indexable problems are the dual speed problem of Glazebrook, Nino-Mora, and Ansell [24], the maintenance models of Glazebrook, Ruiz-Hernandez, and Kirkbride [25], and the spinning plates and squad models of Glazebrook, Kirkbride, and Ruiz-Hernandez [23]. Our paper is in line with these works in that it trades indexability for specific structural conditions.…”
Section: Indexabilitysupporting
confidence: 62%
“…Many extensions and variations of classical bandit problems have been proposed, including: bandits with a varying finite or infinite numbers of arms (Whittle [78] and Banks and Sundaram [3]), bandits where an adversary has control over the payoffs (Auer et al [2]), bandits with dependent arms (Pandey, Chakrabarti, and Agarwal [57]), bandits where multiple arms can be chosen at the same time (Whittle [79]), bandits whose arms yield rewards even when they are inactive (Glazebrook, Kirkbride, and Ruiz-Hernandez [23]), and bandits with switching costs (Banks and Sundaram [4]). …”
Section: Bandit Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a range of empirical studies have demonstrated the power and practicability of Whittle's approach in a range of application contexts. See, for example, Ansell et al [2], Opp et al [23], Glazebrook et al [14,15], and Glazebrook and Kirkbride [12,13].…”
mentioning
confidence: 99%